A Survey on Self-efficacy in Mathematics of Class XI Students in West Bengal - Kundu, Arup (JOURNAL OF INDIAN EDUCATION, 2019)
The emergent role of self-efficacy in the learning of mathematics has attracted the attention of mathematics educators for a very long time. Students’ self-efficacy in mathematics has been a generator that is known to influence their performance in mathematics. This study has attempted to find out students’ self-efficacy in mathematics and further investigate any disparity in self-efficacy between students in different streams of study. The population for the study was Class XI students in the southern districts of West Bengal. The sample consisted of 784 students, both boys and girls from randomly selected 24 schools. The tool used is titled Mathematics Self-efficacy Questionnaire. The results show that self-efficacy in mathematics of students with different streams of study is significantly different. In particular, science students have the highest self-efficacy while that of Arts students, and there is significant gender wise difference in self-efficacy in favour of boys.